Real-world safety profile of etelcalcetide in dialysis-related secondary hyperparathyroidism: a pharmacovigilance analysis of FAERS data - Cong Zou; Xing Wang; Ruizhen Huang; Honglin Hu (Renal Failure)
Purpose The real-world safety of etelcalcetide in the treatment of dialysis-related secondary hyperparathyroidism (SHPT) was evaluated by analyzing associated adverse events (AEs) and assessing their clinical significance.Methods Data from the U.S. Food and Drug Administration Adverse Event Reporting System (FAERS) (2017–2024) were analyzed. Disproportionality analysis was performed using reporting odds ratio (ROR), proportional reporting ratio (PRR), multi-item gamma-Poisson shrinker, and Bayesian confidence propagation neural network. Subgroup analysis, time-series analysis, and clinical prioritization assessment were conducted to identify high-risk events.Results Among 2,525 etelcalcetide-related AE reports, the most frequently reported events were hypocalcemia, gastrointestinal discomfort, and cardiovascular (CV) complications. Newly identified safety signals included sepsis (ROR 134.24), aspiration pneumonia (ROR 8.88), cerebral hemorrhage (ROR 5.47), and bile duct stones (ROR 51.57). Time-series analysis revealed a peak in AE incidence within the first 30 days (23.45%), predominantly involving hypocalcemia, gastrointestinal reactions, and CV events, emphasizing the need for early treatment monitoring. Long-term use (>360 days) was associated with higher risks of infections and CV complications. Clinical prioritization analysis identified ventricular fibrillation (score = 6) as the highest-priority event, while heart failure and sepsis (score = 5) were classified as moderate-priority events requiring close monitoring.Conclusion Etelcalcetide use is associated with an elevated risk of hypocalcemia, infections, and CV events, particularly within the first 30 days of treatment. Close monitoring in both early and long-term phases is essential for optimizing safety management. These findings provide valuable real-world evidence, underscoring the necessity of further research to refine clinical safety strategies.